Como as mudanças climáticas poderão afetar a fotossíntese líquida de espécies arbóreas da Floresta Atlântica? Experimentos em jardins comum e utilização da espécie Myrsine coriacea como modelo - Pereira, Jéssica Priscilla (2022)
The understanding of how tropical dioecious species cope with different environmental conditions is still limited. The inability to cope with adverse conditions can lead to decreased performance (photosynthetic and growth) and reproductive success, causing population declines. The objective of this work was to study how the environmental variations, verified along an altitude gradient, affect the photosynthetic capacity of the dioecious species Myrsine coriacea. In the first stage of the study (Chapter 1), we investigated how the attributes of secondary traits of the dioecious species M. coriacea vary in an altitudinal gradient. Eighty plants (40 males and 40 females) were selected from seven natural populations. Leaf morphological and stomatal characteristics and isotopic composition of carbon (δ13C) and nitrogen (δ15N) were analyzed. Female plants showed higher δ 13C and δ15N compared to males, a result associated with a higher carboxylation capacity. Plants of both sexes had smaller stomata and greater water use efficiency at higher altitudes, lower δ15N and higher carbon-nitrogen ratios at lower altitudes. Stomatal and venation characteristics showed a lack of coordination, which was compensated by variation in specific leaf area. In the second step (Chapter 2), we determined 33 functional characteristics related to photosynthetic performance (ten leaf characteristics, seven anatomical characteristics and 16 related to gas exchange and chlorophyll a fluorescence) of M. coriacea plants from four altitudes of origin. (630, 910, 1229 and 2019 m) cultivated in a common garden located at high (HA; 914 m) and low altitude (LA; 108 m). In LA there was mortality of all plants from 2019 m. Net CO2 assimilation and dark respiration were higher in HA compared to LA, regardless of the altitude of origin. Plants in LA showed a higher oxidative pressure on the photosynthetic machinery (higher ratio ETR/Ag) compared to plants in HA, regardless of the altitude of origin. In LA, regardless of the altitude of origin, photorespiration represented approximately 60% of gross photosynthesis, a value 50% higher than that observed in plants in HA. In HA, plants from 2019 m showed local adaptation in leaf characteristics (lower specific leaf area and stomata size; higher trichome density) that were related to lower transpiration and photosynthetic capacity. We conclude that, with the increase in temperature as a result of climate change, plants at higher altitudes will have a lower adaptive capacity, while plants at low/medium altitudes will respond with morphological changes, avoiding water deficit. However, these modifications may limit the photosynthetic capacity and increase the possibility of oxidative stress.